The dynamic communities of oral microbiome in neonates - Guo, Haiying; Li, Jin; Yao, Hantao; Liu, Yina; Ji, Yaoting; Zhang, Jing; Zhao, Yun; Du, Minquan (Frontiers in Microbiology, 2022)
The oral microbiome, associated with both oral disease and systemic disease, is in dynamic status along the whole life, and many factors including maternal microbiomes could impact the oral microbiome. While fewer studies have been conducted to study the characteristics of the oral microbiome in neonates and the associated maternal factors. Hence, we collected the microbiome of 15 mother-infant pairs across multiple body sites from birth up to 4 days postpartum and used high-throughput sequencing to characterize the microbiomes in mothers and their neonates. The oral microbiome in the neonates changed obviously during the 4 days after birth. Many bacteria originating from the vagina, skin, and environment disappeared in oral cavity over time, such as Prevotella bivia and Prevotella jejuni. Meanwhile, Staphylococcus epidermidis RP62A phage SP-beta, predominate bacterium in maternal skin microbiome and Streptococcus unclassified, main bacterium in vaginal microbiome, obviously increased in neonatal oral microbiome as time went on. Interestingly, as time progressed, the composition of the oral microbiome in the neonates was more similar to that of the milk microbiome in their mothers. Moreover, we found that the changes in the predominant bacteria in the neonates were in line with those in the neonates exposed to the environment. Together, these data described the sharp dynamics of the oral microbiome in neonates and the importance of maternal efforts in the development of the neonatal microbiome.